2023
DOI: 10.1161/circulationaha.123.064155
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pericytes Acquire a Fibrogenic Phenotype and Contribute to Vascular Maturation After Myocardial Infarction

Abstract: BACKGROUND: Pericytes have been implicated in tissue repair, remodeling, and fibrosis. Although the mammalian heart contains abundant pericytes, their fate and involvement in myocardial disease remains unknown. METHODS: We used NG2 Dsred ;PDGFRα EGFP pericyte:fibroblast dual reporter mice and inducible NG2 CreER mice to study the fate and phenotypic modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…6 However, no bona fide pericyte-derived fibroblasts, ie, with loss of mural cell markers and upregulation of fibroblast lineage markers, were identified. Here, Alex et al 11 report a similar process of pericyte activation, and uncover that at day 7 after MI, a subset of pericytes coexpressing fibroblast marker PDGFRα EGFP expressed some extracellular matrix genes to a greater extent than activated fibroblasts. Also, 16.6% of infarct myofibroblasts, defined as elongated α-SMA + cells located outside the vascular wall, were NG2 CreERlineage-traced.…”
Section: Future Studies and Perspectivesmentioning
confidence: 55%
See 4 more Smart Citations
“…6 However, no bona fide pericyte-derived fibroblasts, ie, with loss of mural cell markers and upregulation of fibroblast lineage markers, were identified. Here, Alex et al 11 report a similar process of pericyte activation, and uncover that at day 7 after MI, a subset of pericytes coexpressing fibroblast marker PDGFRα EGFP expressed some extracellular matrix genes to a greater extent than activated fibroblasts. Also, 16.6% of infarct myofibroblasts, defined as elongated α-SMA + cells located outside the vascular wall, were NG2 CreERlineage-traced.…”
Section: Future Studies and Perspectivesmentioning
confidence: 55%
“…5 However, in mice, genetic ablation of Tgfbr2 in the NG2 lineage did not affect pericyte-to-myofibroblast transition or infarct scar size. Instead, Alex et al 11 observed reduced numbers of pericytes encircled by forming arterioles. This was associated with reduced coverage of vessels by vascular support cells, vessel dilation, increased infiltration of macrophages, and increased left-ventricular enddiastolic volume 1 week after infarction.…”
Section: Figure Pericyte Activation After Myocardial Infarctionmentioning
confidence: 97%
See 3 more Smart Citations